Effects of Vitamin C Supplementation on Histology of Callus Diameter and Osteoblast Number in Male Wistar Rats With Complete Femur Bone Fracture - Rambe, Syahrul Ramadan; Putra, Reza Mahruzza; Rahmadhany, Heru (Journal of Biomedicine and Translational Research, 2025)
Background: The role of nutritional factors, particularly vitamin C, in bone repair has been extensively studied. However, despite this research, the specific impact of vitamin C on bone fracture healing remains unclear. While some studies suggest that vitamin C supplementation may enhance bone repair, others report no significant benefits.Objective: This study aimed to investigate the effects of different doses of vitamin C on callus formation and osteoblast proliferation in a rat femur fracture model.Methods: A post-test-only control group design was employed in this study, involving 27 male Wistar rats that were randomly divided into three groups. The first and second groups received daily intramuscular injections of vitamin C at doses of 200 mg/kg body weight (BW) and 500 mg/kg BW, respectively, following femur bone fracture and fixation. The control group did not receive vitamin C and underwent no fixation. After 14 days, all rats were euthanized, and their femur bones were histologically examined for callus diameter and osteoblast count.Results: Vitamin C supplementation significantly increased the callus diameter in rats with complete femoral fractures. Both the 200 mg and 500 mg doses proved effective, demonstrating a clear dose-response relationship. Additionally, Vitamin C significantly elevated the number of osteoblasts, which play a crucial role in bone formation. However, there was no statistically significant difference in osteoblast count between the 200 mg and 500 mg doses.Conclusion: In conclusion, vitamin C supplementation has been shown to positively influence bone fracture healing in rats by promoting an increase in callus diameter and enhancing osteoblast proliferation. This study indicates that vitamin C could serve as a beneficial adjunct therapy for facilitating bone fracture healing, particularly by improving callus formation. Physicians should consider integrating vitamin C into treatment plans for patients with fractures, using doses similar to those applied in this study, adjusted appropriately for human use.